High school mathematics texts construction of statistics practices - Weiland, Travis (Frontiers in Education, 2023)
Introduction A robust understanding of statistics has become crucial in our data centric societies. In the school setting the teaching of statistics is situated within the mathematics curriculum in the U.S. However, many mathematics teachers often have little to no past experiences with statistics before teaching it. Given such circumstances, textbooks likely play a strong role influencing the statistics curriculum teachers enact for students. In this study, I investigate how the discourse of two common high school textbook series form what the actions are for doing statistics. Methods For this study I used a Foucauldian discourse analysis to inductively analyze the texts for the actions they create. Results One of the main results of the study was that the actions are very routinized/algorithmic in nature. Furthermore, most actions were associated with analyzing data. I also contrast the findings of the analysis to the discourse of the field of statistics education, namely through the Guidelines for Assessment and Instruction in Statistics Education, which highlighted some significant absences including statistical questions to drive investigation and discussion of collecting data. Discussion The findings have implications for teacher education in terms of topics to focus teachers’ attention on and to help provide them further support with teaching to their students.